Analysis on Students Vocabulary Mastery of Students Hospitality in Vocational High School 4 at Tenth Grade Students Jambi City - Armita, Putri Rahmawati (JELT: Journal of English Language Teaching, 2024)
This research aims to find out how students’ hospitality vocabulary mastery at Vocational High School 4 Jambi City. This type of the research is a quantitative descriptive research method with a total population of 69 people. Through a simple random sampling technique, 33 students of Class X PH 1 were selected to be sampled who will be representative of the population. The data were collected by using tests. The test is given to know students’ ability in vocabulary mastery. It is multiple-choice and consists of fifty questions. The result of this research is students’ vocabulary mastery test in English subject obtained a total score of 1794 with an average of 54,48. It means that students’ vocabulary mastery is good enough.Keywords: Vocabulary Mastery, Students Hospitality